2016
DOI: 10.1097/md.0000000000003761
|View full text |Cite
|
Sign up to set email alerts
|

Use of Traditional and Complementary Medicine as Self-Care Strategies in Community Health Centers

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…This finding can be explained by the fact that higher SES individuals can afford to buy medicinal herbs due to their higher ability to pay. This observation is consistent with previous studies, in which affordability is one of the most important factors for MH usage [ 17 19 , 31 , 32 ]. A study on the use of herbal medicine in Taiwan indicated that CHM use among pregnant women with a higher level of education and larger income had greater rates of CHM usage [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…This finding can be explained by the fact that higher SES individuals can afford to buy medicinal herbs due to their higher ability to pay. This observation is consistent with previous studies, in which affordability is one of the most important factors for MH usage [ 17 19 , 31 , 32 ]. A study on the use of herbal medicine in Taiwan indicated that CHM use among pregnant women with a higher level of education and larger income had greater rates of CHM usage [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, as we have mentioned, inappropriate use of supplements may lead to adverse outcomes ( 44 ). In addition, with increasing health literacy, respondents expressed uncertainty about the usefulness of these supplements ( 45 ). Therefore, how do we provide scientifically based health guidance to older people that addresses their needs in the future?…”
Section: Discussionmentioning
confidence: 99%
“…Variables of health habits include (1) self-care in TCM (yes or no) and (2) recent alcohol consumption (yes or no). Self-care in TCM includes massaging, emotional therapy, dietary supplement usage, traditional sports therapy and other supplementary approaches to remain healthy in daily life as the philosophy of TCM suggests [28]. Recent alcohol consumption refers to drinking alcohol at least once a week in the previous 6 months and more.…”
Section: Materials and Variablesmentioning
confidence: 99%
“…Due to the fewer side effects of TCM, the higher satisfaction with the doctors' communication skill [47,48], and the expectation of removing the root of disease and health promotion, some of the Chinese people, especially the elderly, prefer to seek treatment in TCM sectors [22] or resort to some folk remedies [49] through word of mouths. Elders with the habits of self-care in TCM have higher affinities to TCM [28], and these elders tend to seek medical help in TCM sectors, in which they may be confronted with less barrier during the process of seeing doctors compared with the western medicine sectors [47,48], especially for empty-nest elders without support from younger family caregivers [15]. This finding may explain the lower rate of self-treatment among elders with higher affinities for TCM in this empty-nest subgroup.…”
Section: Subgroups Of Empty-nest and Non-empty-nest Eldersmentioning
confidence: 99%